Ethnic Minority Muslim Social Pedagogy (Counter-radicalism of Chinese Muslims through Islamic Education) (EDUKASIA, 2020)
This paper aims to discuss the efforts of Chinese Muslims in practicing Islamic education in their minority communities. By using a social pedagogical approach model in Islamic education, Chinese Muslims make social and cultural issues a starting point for religious understanding. As a minority social entity, Chinese Muslims who are members of PITI (Indonesian Chinese Muslim Association), also try to transmit their Islamic knowledge not co-opted by radical Islamic religious doctrines. By using qualitative-phenomenological research methods, this study has succeeded in finding that this minority Muslim community's social pedagogy realizes by involving three elements simultaneously: teaching, acculturation, and social action in Islamic education. Through this strategy, Chinese Muslims try to become devout Muslims without reducing their cultural reality as a Chinese. In another position, the Chinese Muslim social pedagogy approach seeks to carry out the de-radicalization movement using socio-cultural instruments through academic activities in Islamic education.